Implementation of Community Policing by The Narcotics Investigation Unit of Polresta Bogor Kota In Drug Abuse Prevention - Haminda Andea Nur; Monica Margaret (Journal of Law, Politic and Humanities, 2024)
This study aims to describe the implementation of community policing in drug abuse prevention in Cikaret Village. This study uses a qualitative approach with a case study method. Data were collected through observation, interviews, and document study. The study findings indicate that community policing has been implemented by the Narcotics Investigation Unit through the Drug-Free Village Program. The program generally succeeded in reducing the intensity of drug abuse cases. This was driven by the establishment of partnerships between the police, the community, and stakeholders. The partnership between the police and the community is reflected in the empowerment of the community to become members of Drug-Free Village task force. There are obstacles in the implementation of the program, including the lack of community participation, limited budget to support positive activities, the lack of police approach with the surrounding community, and the low intensity of patrols by the police. Therefore, to streamline community policing, the synergy between the police, community, and stakeholders needs to be strengthened.